O que fazem com as TIC as lideranças da escola pública portuguesa? - Santos, José Rui (2019)
At the end of this second decade of the 21st century, more than questioning the entry of information and communication technologies (ICTs) in schools, we question how should schools appropriate and use them. Within this scope school leaderships play an especially relevant role, since the way the school appropriates and takes better advantage of them strongly depends on the way leaderships deal with ICTs, the importance they give to them and the boost and guidance they provide for their use. This article derives from a multiple case study, in the non-higher education, with mixed, mainly qualitative and descriptive, methodology, aiming at studying what is the type of appropriation of ICTs by Portuguese public-school leaderships. The main sources for data collection were mixed questionnaires and semi-structured interviews, and, also, documentary analysis of institutional documents of the study cases. The analysis and interpretation of the data extracted from these documents were carried out through documentary analysis techniques. The analysis and interpretation of the data collected with the questionnaires (statistical analysis) was carried out with the software Statistical Package for the Social Sciences (SPSS), and the analysis and interpretation of the interviews’ data through the content analysis technique. Two conclusions stand out from the study, which even if they might be internal to the study cases, they may be observed in the majority of the non-grouped schools/school groups in Portugal: the level of appropriation and exploitation of the ICTs potential depends much more on the action of leaderships than on political impositions, or education policies, and the pressure for their use exercised by local education communities; technological and digital tools exist and are ever more accessible and user-friendly, using them and taking the best advantage out of them depends, mainly, from whether or not the school leaderships are technological leaderships.